Pengaruh Moral Ekonomi dan Kewirausahaan Nelayan Terhadap Perilaku Ekonomi Rumah Tangga Nelayan di Pantai Kenjeran Surabaya Jawa Timur - Tri Andjarwati (Universitas 17 Agustus 1945 Surabaya, 2017)
Kenjeran Beach in Surabaya is one of the areas that has potential in the sector offishery is large enough. Fisheries on the coast of Kenjeran Surabaya include marinefisheries, public waters. Therefore the utilization of fish resources optimized rationally soas to improve the welfare for the fishermen's income. This study talks about the Effect of Economic Morale and Degree of Entrepreneurshipon Fisherman Household Economic Behavior at Kenjeran Beach Surabaya East Java.The population of this research is 624 fishermen in Kenjeran SurabayaThe determination of the number of samples based on a simple random method with Slovinformula with dispersion of 5% resulted in a total sample of 244 peopleFrom the results of model testing in this study, with estimation of Generalized Least SquareEstimation (GLS), structural equation model analysis (SEM), proportional randomsampling method and software assistance Amos 22, on 244 respondents. The resultsshowed that: 1). Economic morals affect the degree of entrepreneurship of fishermen inKenjeran Surabaya. 2). Economic morals affect the behavior of fishermen economy inKenjeran Surabaya. 3). The fisherman entrepreneurship significantly influences thebehavior of fishermen economy in Kenjeran Surabaya. 4). Economic morals have anindirect effect on economic behavior through fishing entrepreneurship in KenjeranSurabaya.Key words: Moral economy of fisherman, entrepreneurship of fisherman, economic behavior